User Behavior in Using Mobile Commerce (Scale Development: Perspective of Trust and Risk) - Setiawan Assegaff; Jasmir Jasmir; Dodo Zaenal Abidin; Sharipuddin Sharipuddin (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
The aim of ours research is to explore the relation between the elements of trust and risk and their impact on consumer behavior in the intention of use of mobile commerce services based on sales. The final goal of this research is to understand consumer behavior in the use of mobile commerce application services in Indonesia by considering the elements of trust and risk in consumer behavior. Finding from previous research have revealed that trust and risk is one of the critical aspects in the use of e-commerce services. This article focus is to discuss the development stages of research instruments development to be used in next survey agenda. By applying Technology Acceptance Model (TAM) as a theoretical basis of a conceptual model and the research instrument was developed. Models and instruments then validated through a pilot study involving 75 students as respondents. Survey data were analyzed via Smart-PLS software version 2 to ensure reliability level and validity of the instrument. This study resulted in a validated instrument that will be used to collect data from actual surveys